MPLIKASI KASUS SENGKETA MEREK WD-40 DITINJAU DARI UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS (CONTOH KASUS NOMOR 39/PDT.SUS.MEREK/2018/PN.NIAGA.JKT.PST. - Muhammad Alkindi Soramoes; Christine S.T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2021)
The case of a trademark dispute between WD-40 and Get-All-40 proves that there is still a gap in trademark infringement by irresponsible parties, or parties who hitch a ride on well-known brands in bad faith. The problem faced is what is the implication of Law Number 20 of 2016 concerning Trademarks and Geographical Indications for famous trademark disputes related to the WD-40 COMPANY and WD-40 Manufacturing Company cases. The research method used is normative juridical legal research. The results of the study show that the implications of Law Number 20 of 2016 concerning Trademarks and Geographical Indications for famous trademark disputes related to the WD-40 COMPANY and WD-40 Manufacturing Company cases, where this trademark dispute was resolved / broken by the judge with the victory of the Plaintiff WD- 40 Company and WD-40 Manufacturing Company which in this case the judge canceled the registration of the Defendant's